Literature review - Liu, Yao (Penerbit UMP, 2017)

(untitled)
This module presents a step-by-step guidance for conducting a literature review for postgraduate research at both Master’s and PhD’s level. After introducing what literature review is, it starts from selecting a review concept, searching literature, analyzing/synthesizing literature, to writing a literature review as well as listing references. The module ends with evaluating good literature review and some ethical issues.